Molecular porphyrinic freestanding buckypaper electrodes from carbon nanotubes for glucose fuel cells - Elouarzaki, Kamal (2017)
An original strategy for the design of free standing buckypapers using unique molecular catalysts was developed. Pyrene-modified metalloporphyrins enable the formation of stable buckypapers using carbon nanotubes for the oxidation of glucose and reduction of oxygen. The developed molecular buckypapers show high performances and an excellent stability in a glucose fuel cell setup.